Modifying Tank Model for Study on the Land Use Change Effect to Runoff - . Harmalis; M. Azron Dhalhar; M. Yanuar J. Purwanto (Jurnal Keteknikan Pertanian, 2001)
The objectives of the research were to modiv the tank model by using infiltration process in the model, based on available daily rainfall data, actual evapotranspiration rates, in 1996 and 1997 for the Cidanau Watershed. The hydrological data were the primary and secondary data. In this study, the prediction of the daily river runoff / discharge was developed by using the modified tank model of the rainfall-runoff processes, and applied to simulate the three land use types in the Cidanau Watershed, comprising of 22 620 Ha. The average coefficient of correlation is 0.81 for the model calibration and validation. The model can also be used to predict river discharge for different land use.